Penerapan Media Pembelajaran menggunakan Papan Peluang, Dadu, dan Multimedia Pembelajaran Interaktif dengan Pendekatan RME di SMA Swasta PAB 8 Saentis Percut - Kairuddin, Kairuddin; Samosir, Martha Indah; Sitorus, Grace Elicia; Sihotang, Harry Marcel Wahyu; Tanjung, July Yanty (Mandalika Mathematics and Educations Journal, 2024)
This research aims to implement probability learning media based on Realistic Mathematics Education (RME) at SMA Swasta PAB 8 Saentis Percut. The problem addressed is students' difficulties in understanding the abstract and complex concept of probability. The method used is qualitative with a case study approach, involving observation, interviews, and student satisfaction surveys. The results show significant improvement in students' understanding of probability concepts, as well as increased motivation and active participation in learning. In conclusion, RME-based learning media effectively helps students contextualize and apply probability, enhancing engagement and facilitating deeper understanding.